Review of Teiid Morphology with a Revised Taxonomy and Phylogeny of the Teiidae (Lepidosauria: Squamata) - Harvey, Michael B.; Ugueto, Gabriel N.; Gutberlet, Jr., Ronald L. (Zootaxa, 2012)
Despite advances within particular groups, systematics of the Teiidae has long been unsatisfactory, because fewmorphological characters have been described for this family. Consequently, most species have been assigned to the large,polyphyletic, and poorly defined genera Ameiva and Cnemidophorus. We describe 137 morphological characters andscore them for most species of Neotropical Teiidae. Important, but previously undescribed, character suites include pupilshape; the frontal ridge; longitudinal division of the interparietal; the rostral groove; patterns of supraciliary fusion; thepreauricular skin fold; the “toothy” first supralabial; modified apical granules; the pectoral sulcus; expansion of scales atthe heel; tibiotarsal shields; scales between the digital lamellae along the postaxial edges of the toes; scale surfacemicrostructure of macrohoneycomb, macroridges, or lamellae; distribution patterns and morphology of lenticular scaleorgans; types of epidermal generation glands; and several hemipenial structures. We propose a new taxonomy of theTeiidae based on recovered evolutionary history and numerous morphological characters surveyed in this study. Werecognize three subfamilies: Callopistinae new subfamily, Teiinae Estes et al., and Tupinambinae Estes et al. To resolvepolyphyly of Ameiva and Cnemidophorus, we erect four new genera for various groups of Neotropical Teiidae: Ameivulanew genus, Aurivela new genus, Contomastix new genus, and Medopheos new genus. We resurrect Holcosus Cope fromthe synonymy of Ameiva and Salvator Duméril and Bibron from the synonymy of Tupinambis. On the basis of sharedderived characters, we propose new species groups of our redefined Ameiva and Cnemidophorus. We incorporate our newcharacters into a key to the genera and species groups of Teiidae. A phylogenetic hypothesis of Teiidae based onmorphological characters differs substantially from hypotheses based on mitochondrial DNA. The phylogeny based onmorphology is consistent with well-established biogeographic patterns of Neotropical vertebrates and explains extreme morphological divergence in such genera as Kentropyx and Aurivela.